2021
DOI: 10.3390/foods10030678
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Sheep Milk Ice Cream with Inulin and Apple Fiber

Abstract: The aim of the study was to assess the effect of the addition of inulin and the replacement of part of the inulin with apple fiber on the physicochemical and organoleptic properties of ice cream. Moreover, the survival of Bifidobacterium animalis ssp. Lactis Bb-12 and Lactobacillus rhamnosus was studied in sheep milk ice cream. There was no effect of the apple fiber and the type of bacteria on the number of bacteria in the probiotics after fermentation. As a result of freezing, in the mixture containing Bifido… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 49 publications
1
16
0
Order By: Relevance
“…Sabet-Sarvestani et al [ 20 ] produced synbiotic ice cream using Lactobacillus casei/Lactobacillus plantarum and fructooligosaccharides, and they observed a beneficial role of these prebiotics for the growth of probiotics. Kowalczyk et al [ 34 ] observed that the survival of Bifidobacterium animalis ssp. lactis BB-12 in sheep’s milk ice cream at the 21st day of storage exceeded log 10 CFU/g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sabet-Sarvestani et al [ 20 ] produced synbiotic ice cream using Lactobacillus casei/Lactobacillus plantarum and fructooligosaccharides, and they observed a beneficial role of these prebiotics for the growth of probiotics. Kowalczyk et al [ 34 ] observed that the survival of Bifidobacterium animalis ssp. lactis BB-12 in sheep’s milk ice cream at the 21st day of storage exceeded log 10 CFU/g.…”
Section: Resultsmentioning
confidence: 99%
“…The production of ovine’s and caprine’s yoghurts and frozen yoghurts has also followed this trend. Several research works refer to the use of ewe’s [ 32 , 33 , 34 , 35 , 36 , 37 ] and goat’s [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ] milks in the production of ice creams with functional properties. In addition, several authors reported the potential medicinal properties of small ruminant’s milks and dairy products [ 51 , 52 , 53 ].…”
Section: Introductionmentioning
confidence: 99%
“…The color of raw goat’s milk, milk with collagen and collagen hydrolysate addition and after fermentation, was determined by a colorimeter (Precision Colorimeter, Model NR 145, Shenzhen, China) using the CIE L*a*b* system. The following parameters were determined: L*—as lightness (from 0—black to 100—white), a*—as color from red (+) to green (−), b*—as color from yellow (+) to blue (−), C—as color purity and intensity, and h 0 —as color hue [ 85 ]. Before measurement, the device was calibrated on a white reference standard [ 86 ].…”
Section: Methodsmentioning
confidence: 99%
“…Apples contain a balanced and high amount of soluble and insoluble dietary fibers. Among them, the water-soluble pectin is a polysaccharide which is not digested by enzymes in the human digestive system and provides colonization of probiotic bacteria as a prebiotic source in the large intestine (Kowalczyk et al 2021;Zahid et al 2021). While apples contain approximately 2-3 grams of dietary soluble fiber per 100 g, of which 50% is pectin, they are also an excellent source of phytochemicals.…”
Section: Introductionmentioning
confidence: 99%
“…While apples contain approximately 2-3 grams of dietary soluble fiber per 100 g, of which 50% is pectin, they are also an excellent source of phytochemicals. The fiber found in apples combined with other apple nutrients could be fermented into short-chain fatty acids (SCFAs) that help to enhance the growth of beneficiary gut bacteria (Chung et al 2017;Kowalczyk et al 2021).…”
Section: Introductionmentioning
confidence: 99%